Detection of aneuploidies by paralogous sequence quantification. Issue 12 (9th December 2004) - Deutsch, S; Choudhury, U; Merla, G; Howald, C; Sylvan, A; Antonarakis, S E
Abstract : Background: Chromosomal aneuploidies are a common cause of congenital disorders associated with cognitive impairment and multiple dysmorphic features. Pre-natal diagnosis of aneuploidies is most commonly performed by the karyotyping of fetal cells obtained by amniocentesis or chorionic villus sampling, but this method is labour intensive and requires about 14 days to complete. Methods: We have developed a PCR based method for the detection of targeted chromosome number abnormalities termed paralogous sequence quantification (PSQ), based on the use of paralogous genes. Paralogous sequences have a high degree of sequence identity, but accumulate nucleotide substitutions in a locus specific manner. These sequence differences, which we term paralogous sequence mismatches (PSMs), can be quantified using pyrosequencing technology, to estimate the relative dosage between different chromosomes. We designed 10 assays for the detection of trisomies of chromosomes 13, 18, and 21 and sex chromosome aneuploidies. Results: We evaluated the performance of this method on 175 DNAs, highly enriched for abnormal samples. A correct and unambiguous diagnosis was given for 119 out of 120 aneuploid samples as well as for all the controls. One sample which gave an intermediate value for the chromosome 13 assays could not be diagnosed. Conclusions: Our data suggests that PSQ is a robust, easy to interpret, and easy to set up method for the diagnosis of common aneuploidies, and can be performed in less than 48 h, representing a competitive alternative for widespread use in diagnostic laboratories.